'Models of' and 'Models for': On the Relation between Mechanistic Models and Experimental Strategies in Molecular Biology. (15th March 2018) - Ratti, Emanuele
Abstract: Molecular biologists exploit information conveyed by mechanistic models for experimental purposes. In this article, I make sense of this aspect of biological practice by developing Keller's idea of the distinction between 'models of' and 'models for'. 'Models of (phenomena)' should be understood as models representing phenomena and are valuable if they explain phenomena. 'Models for (manipulating phenomena)' are new types of material manipulations and are important not because of their explanatory force, but because of the interventionist strategies they afford. This is a distinction between aspects of the same model. In molecular biology, models may be treated either as 'models of' or as 'models for'. By analysing the discovery and characterization of restriction–modification systems and their exploitation for DNA cloning and mapping, I identify the differences between treating a model as a 'model of' or as a 'model for'. These lie in the cognitive disposition of the modeller towards the model: a modeller will look at a model as a 'model of' if interested in its explanatory force, or as a 'model for' if interested in the material manipulations it can possibly afford. 1 Introduction 2 'Models of' and 'Models for' in Molecular Biology 2.1 'Models of' in molecular biology 2.2 'Models for': The case of CRISPR–Cas9 2.3 Importance of 'models for' 2.4 'Models for' and philosophy of experimentation in biology 3 'Models for' and the Discovery of Restriction–Modification Systems 3.1 A tale of three Nobel Laureates 3.2 Restriction–modification system model as a 'model of' and a 'model for' 4 Epistemic Disposition and Disposition towards Affordances 4.1 Two cognitive dispositions towards models 4.2 Intentions in philosophy of science and studies of scientific cognition 5 Virtues of 'Models for' 5.1 'Models for', target systems and portability 5.2 How-possibly models and schemas 6 Conclusion